Pengaruh Kompetensi Personal Guru Bimbingan dan Konseling Terhadap Aktivitas Belajar Siswa - Decky Roland Heristyan; Titin Swatinah; Siti Rahayu (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2021)
The teacher is the most decisive component in the education system as a whole, which must receive central attention, first and foremost. Personal competence or personality personal competence is the quality of a teacher's personal abilities needed to become a good teacher. This personal competence includes personal abilities related to self-understanding, self-acceptance, self-direction, and self-realization. The purpose of this study is to determine the effect of the personal competence of guidance and counseling teachers on class student learning activities. The population in this study was 145 students of class VIII SMP Negeri 2 Silo. The research sample was selected as many as 50 students by random sampling method. The data were analyzed using Chi Square (Chi Square) statistical analysis. The results specifically show that personal physical competence has a weak effect, while personal and psychological competence has a significant effect. Recommendations in this study are expected that further research can correct the shortcomings of this study.  Keywords:Counselor Competence; Junior High School